2000
DOI: 10.1002/1531-8249(200005)47:5<670::aid-ana20>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mutation type and X chromosome inactivation on Rett syndrome phenotypes

Abstract: We screened 71 sporadic and 7 familial Rett syndrome (RTT) patients for MECP2 mutations by direct sequencing and determined the pattern of X chromosome inactivation (XCI) in 39 RTT patients. We identified 23 different disease‐causing MECP2 mutations in 54 of 71 (76%) sporadic patients and in 2 of 7 (29%) familial cases. We compared electrophysiological findings, cerebrospinal fluid neurochemistry, and 13 clinical characteristics between patients carrying missense mutations and those carrying truncating mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
179
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(191 citation statements)
references
References 38 publications
6
179
1
3
Order By: Relevance
“…Consistent with the sporadic occurrence of RTT, most of these mutations occurred de novo at CpG mutation hotspots. 4,5 The majority of the single-nucleotide substitutions are C to T transitions at CpG sites (R106W, R133C, T158M, R306C, R168X, R255X) (71% of all identified MECP2 mutations). 3,6 These sites are hypermutables.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with the sporadic occurrence of RTT, most of these mutations occurred de novo at CpG mutation hotspots. 4,5 The majority of the single-nucleotide substitutions are C to T transitions at CpG sites (R106W, R133C, T158M, R306C, R168X, R255X) (71% of all identified MECP2 mutations). 3,6 These sites are hypermutables.…”
Section: Introductionsupporting
confidence: 84%
“…14 Recently, results reported by Amir and colleagues using a more time consuming approach based on the analysis of somatic cell hybrids retaining either the maternal or the paternal X chromosome showed a paternal origin in two cases and a maternal origin in one sporadic case. 5 Moreover, data showing similar results were presented at the American Congress of Human Genetics in Philadelphia. From 26 sporadic cases with a clinical diagnosis of Rett syndrome, 23 have been shown to be from a paternal origin.…”
Section: Discussionmentioning
confidence: 99%
“…During normal development, one X chromosome in each cell randomly becomes inactivated, and females display a mosaicism of cells with either paternal or maternal X chromosomes. In the case of RTT, variability in the inactivation of the WT or mutant MeCP2 leads to a spectrum of phenotypic severity (7)(8)(9). Indeed, females with RTT often exhibit nonrandom activation of X chromosomes favoring the WT allele and resulting in subdued phenotypes (9).…”
mentioning
confidence: 47%
“…Most studies have found an association between skewed X inactivation and a milder phenotype, 17,26,28,31 whereas one study also found an association between skewed X inactivation and a more severe phenotype. 28 Our results support the reported association between a milder phenotype and skewed X inactivation, as we found a higher mean degree of skewing in mild cases than in moderate or severe cases.…”
Section: Discussionmentioning
confidence: 99%